IMPLIKATUR PERCAKAPAN DALAM NOVEL “SEORANG LAKI-LAKI YANG KELUAR DARI RUMAH” KARYA PHUTUT EA: CONVERSATIONAL IMPLICATURE IN THE NOVEL ‘SEORANG LELAKI YANG KELUAR DARI RUMAH’ BY PHUTUT EA - Tupong, Indra S.; Salam; Asri, Aswati (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research aims to describe the use of conversational implicatures in the novel